Analysing intermediary organisations and their influence on upgrading in emerging agricultural clusters. (September 2018) - Ramirez, Matias; Clarke, Ian; Klerkx, Laurens
This paper analyses intermediary organisations in developing economy agricultural clusters. The paper critically engages with a growing narrative in studies of intermediaries that have stressed the ownership structure of intermediaries as a key driver for enabling knowledge transfer, inter-firm learning and upgrading of small producers in clusters. Two case studies of Latin American clusters are presented and discussed. The study suggests that in addition to ownership structure, cluster governance and the embeddedness of intermediaries in clusters are critical factors that need to be taken into account in understanding the influence of intermediaries in the upgrading of small producers in clusters.